A Brief Study on Web Technology (International Journal of Innovative Research in Computer Science & Technology, 2021)
Technology has advanced at a rapid and  efficient pace in recent years. Web technology is one of  the technologies that allow computers to communicate with one another by using markup languages and  multimedia applications. Because it has been noted that  many are uninformed of Web technologies, the author has  opted to highlight the ideas connected to web  technologies in order to address this issue. The author of  this review paper discusses Web technologies and their  different kinds. Browser is included, as well as a  thorough description of its applications. Programming  languages, databases, and data formats are also discussed  in this article. Motion UI, Serverless architecture, and  SPA are just a few of the many trends that will continue  in future. Web is adopting new technologies such as  Artificial Intelligence (AI), voice search, Blockchain, and  the Internet of Things. As indicated by the technologies  that power the bespoke web software industry, the future  of web technologies is bright.
Keywords: Applications; Browser; Framework; Language; Web Technologies